The Equilibrium Dynamics for an Endogeneous Bid-Ask Spread in a Monopolistic Financial Market - Amaro de Matos, João (2019)
This paper presents an endogeneous model for the stochastic dynamics of the bid-ask spread of prices of financial assets. The model is derived introducing an intermediary and inventory costs in the setting of equilibrium financial markets as described by Platen and Rebolledo (1996).